Narrations of the great companion Haritha bin Wahab Al-Khuzaie, may God be pleased with him, in the six books - study and analysis - - Saleh , Saad (Islamic Sciences Journal, 2023)
Praise be to God, Lord of the worlds, and the best of prayers and blessings be upon our master Muhammad, may God bless him and grant him peace, and upon all his family and companions. This research is about one of the companions of our Prophet, Gods prayers and peace be upon them, who has been honored by the company of the Prophet and by hearing his speech from his honorable mouth, namely, Harith bin wahab AL-Khuzaie may God be pleased with him and his narrations in Six Books (It is astudy and an anlysis) . This research includes an introduction, two articles and aconclusion. The introduction in cludes the importance of the research topic. The first article is dealing with the personal life of Haritha bin wahab and the second article is devoted to his Six navvatives. Finlly, the research ends up with aconclusion that explain the most important results.